A Systematic Analysis of Various Defects and its Sources in Textile Images - M. Fathu Nisha; P. Vasuki, S. Mohamed Mansoor Roomi (Journal of Electronic Design Engineering, 2021)
Fabric is a material which widely used in daily life and manufactured using textile fibers. Textile fibers are made using natural elements such as cotton, wool, and a composite of different elements like wool, nylon, and polyesters. The defect is a flaw formed in the fabric surface during the manufacturing process. Fabric defect is a deformed region that damages the appearance and the fabric performance. The reason for the fabric defects is machine faults, yarn problems, poor finishing, excessive stretching, and color bleeding. This paper has been reviewed the various types of fabric defects and issues that will benefit researchers and practitioners in image processing and computer vision fields in understanding the severity of defects. This review aims to analyze different problems in different textile departments from a quality point of view which is useful for spinning plants, the Textile dyeing industry, and the yarn manufacturing industry.